Satifaction As Intervening For The Antecedents Of Intention To Revisit: Marine Tourism Context In East Java - Achmad Yanu Alif Fianto (RELASI : JURNAL EKONOMI, 2020)
The purpose of this study was to identify the effect of brand experience and service quality on intention to revisit with satisfaction as a mediating variable in the marine tourism in Indonesia. A total of 241 worthwhile questionaires were collected to be used to examine the structural model and the measurement using PLS path modelling analysis. This research was conducted in several coastal tourism objects in East Java, which were emphasized on the north coast of East Java. This study found that service quality has a significant effect on intention to revisit. This study also revealed that at the same time brand experience also had a significant influence on intention to revisit. In addition, this study also revealed that visitor satisfaction was significantly also able to mediate the relationship between service quality with intention to revisit while also having a mediating function of the relationship between brand experience with intention to revisit. This can be interpreted that the coastal tour manager should focus on improving service quality and developing visitor experience in order to enhance tourists' emotional attachments to the coastal tourism area to shove repeat visits among visitors. This research has contributed to an increase in understanding of the effect of service quality and brand experience on intention to revisit by adding satisfaction variables that serve as mediation. In addition, the findings of this study can be very beneficial for the development of coastal tourism in East Java, Indonesia.